Enakshi Ganguly Thukral (ed). Big Dams, Displaced People: Rivers of Sorrow, Rivers of Change. New Delhi: Sage Publications. 1992. 199 pp. Hardbound. Price: Indian Rs 120. (The Pakistan Development Review, 1993)
Big or super dams are considered to be potent symbols of development. These dams, starting with the Hoover Dam constructed in the 1930s in the USA to the Tarbela Dam in Pakistan built during the 1970s, are concrete symbols of man's domination of nature. Currently, there are more than 100 "super dams" in existence around the world. The storage capacity of water in these dams is some 6000 cubic kilometres and the area covered is about 600,000 square kilometres. These dams have significantly contributed to the process of development by helping generate vast quantities of electricity to power industry and to provide irrigation water for agricultural purposes. In addition, these dams have helped control the flow of water, thereby reducing the threat of flooding to those areas situated downstream from the dams. Despite these benefits, however, big dams have come under increasing criticism particularly from environmental and ecological groups. Also, the construction of these dams results in the displacement of large numbers of people, largely from low-income groups, who have to be resettled in other localities. Such resettlements are not without physical and emotional cost to those who have to be relocated, and also to those communities which have to accept these displaced people. It would be appropriate to mention here some of the major dams which have been built in the recent years and which have not come up to the expectations of their proponents. These include the Akosombo Dam in Ghana; the Kainji Dam in Nigeria; and several dams in Central Asia built on rivers that flow into the Aral Sea. These latter dams have caused a decline in the flow of freshwater into the sea, resulting in a fall in the level of water in the Aral Sea. This has destroyed fisheries and has altered the local climate, as well as causing the coastline to retreat.